Quantitation of Six Alternaria Toxins in Infant Foods Applying Stable Isotope Labeled Standards - Gotthardt, Marina; Asam, Stefan; Gunkel, Klara; Moghaddam, Atefeh Fooladi; Baumann, Elisabeth; Kietz, Roland; Rychlik, Michael (Frontiers in Microbiology, 2019)
Alternaria fungi are widely distributed saprophytes and plant pathogens. As pathogens, Alternaria fungi infect crops and vegetables and cause losses in the fields and during postharvest storage. While farmers suffer from declining yields, consumers are endangered by the formation of secondary metabolites, because some of these exhibit a pronounced toxicological potential. The evaluation of the toxicological capabilities is still ongoing and will contribute to a valid risk assessment. Additionally, data on the incidence and the quantity of Alternaria mycotoxins found in food products is necessary for dietary exposure evaluations. A sensitive LC-MS/MS method for the determination of the Alternaria mycotoxins alternariol (AOH), alternariol monomethylether (AME), tentoxin (TEN), altertoxin I (ATX I), alterperylenol (ALTP), and tenuazonic acid (TA) was developed. AOH, AME, and TA were quantified using stable-isotopically labeled standards. TEN, ATX I, and ALTP were determined using matrix matched calibration. The developed method was validated by using starch and fresh tomato matrix and resulted in limits of detection ranging from 0.05 µg/kg to 1.25 µg/kg for starch (as a model for cereals) and from 0.01 to 1.36 µg/kg for fresh tomatoes. Limits of quantification were determined between 0.16 µg/kg and 4.13 µg/kg for starch and between 0.02 µg/kg and 5.56 µg/kg for tomatoes. Recoveries varied between 83 and 108 % for starch and between 95 and 111 % for tomatoes. Intra-day precisions were below 4 % and inter-day precisions varied from 3 to 8 % in both matrices. Various cereal based infant foods, jars containing vegetables and fruits as well as tomato products for infants were analyzed for Alternaria mycotoxin contamination (n = 25). TA was the most frequently determined mycotoxin and was detected in much higher contents than the other toxins. AME and TEN were quantified in many samples, but in low concentrations, whereas AOH, ATX I, and ALTP were determined rarely, among which AOH had higher concentration. Some infant food products were highly contaminated with Alternaria mycotoxins and the consumption of these individual products might pose a risk to the health of infants. However, when the mean or median is considered, no toxicological risk was obvious.